Seismotectonic assessment of the High Atlas orogen: Implications for the 8 September Mw 6.8 El-Haouz earthquake - Skikra, Hamza; Fadil, Abdelali; Ouassanouan, Youness; Lakhouidsi, Khalid; Tahayt, Abdelilah; Soulaimani, Abderrahmane; El Moudnib, Lahcen (Tectonophysics, 2025)
The Moroccan High Atlas is a slowly deforming intracontinental orogenic belt, characterized by moderate and diffuse seismic activity. The 8 September 2023 Mw 6.8 El-Haouz earthquake, one of the most powerful quakes recorded in North Africa, has intensified investigations into the seismotectonics of the High Atlas. This study examines seismotectonic patterns in the High Atlas using seismological and geodetic data to better understand the mechanisms driving such seismic events. Seismological data indicate active shortening in the region, contributing to ongoing mountain building. Present-day deformation is partitioned between thrust and strike-slip faulting, with NW-SE compression, consistent with the broader stress field in North Africa. Frequency-magnitude distribution analysis indicates that the Western High Atlas exhibited low b-values, slightly lower than 1, in the eight years preceding the El-Haouz earthquake, with an low b-value (∼ 0.8 ± 0.1) near the epicenter, suggesting high stress accumulation in the region. GNSS observations reveal that the High Atlas experiences low geodetic velocities compared with the Rif collision belt, with displacements below 1 mm/year. Notably, the axial zone of the Western High Atlas exhibits an uplift of 1.1 mm/yr. The combination of moderate shortening and relatively higher uplift prior to the El-Haouz earthquake suggests that present-day deformation in the Western High Atlas is predominantly accommodated by the reactivation of inherited faults in the axial zone. This is further corroborated by the distribution of aftershocks, which supports a steeply dipping seismogenic fault manifested by the Tizi n'Test Fault. •Moderate shortening and uplift drive present-day deformation in the Western High Atlas.•Low b-values near the El-Haouz epicenter reveal high stress accumulation pre-earthquake.•Active thrust and strike-slip faulting align with NW-SE compression in North Africa.•GNSS data show low geodetic velocities and 1.1 mm/yr uplift in the High Atlas axial zone.•Aftershocks confirm reactivation of steeply dipping faults, e.g., the Tizi n'Test Fault.